Analysis of color properties of raster images of histological microspecimens: own research experience - M.D. Ivanova; M.S. Myroshnychenko; G.I. Khara; O.V. Arseniev; V.O. Olkhovsky; E.K. Grygorian; Yu.Ya. Fedulenkova; S.V. Kozlov (Medičnì Perspektivi)
This study is aimed to develop a computer program to analyze the color properties of raster images of histological microspecimens used in pathological anatomy and forensic medicine. When developing a computer program, we used the system for building client applications – Windows Presentation Foundation (WPF). The system allows you to create applications with visually attractive user interaction capabilities. The programming language is C#, as well as basic graphics capabilities of the .NET Framework system are used. To speed up the display we applied double buffering. In the course of the research, the authors developed a modern computer program «Analysis of color properties of raster images». This program allows you to analyze the color of each individual pixel of a photograph in RGB and Lab color models, comparing the colors and brightness of individual pixels, selecting groups of points and determining statistical characteristics of them. Characteristic points are well distinguishable in the photographs, studied with the program «Analysis of color properties of raster images». This makes it possible to select and automate these properties, using computer recognition algorithms, completely removing human factor’s influence on the analysis results. The computer program «Analysis of color properties of raster images» is of significant scientific and practical interest for specialists both in the field of morphology (pathologists, forensic experts, etc.), and in the field of other biomedical disciplines.